Prevalence of hypertension, obesity and smoking in three Indian communities in northwestern Ontario. - McIntyre, L (1986)
Hypertension is perceived to be an important problem among native people in Canada, but specific prevalence data have not been accumulated. A study was carried out to determine community levels of blood pressure and to document the prevalence of hypertension, obesity and cigarette smoking in nonurban Indians in three communities in northwestern Ontario. Of the 678 people present in the communities at the time of the survey 668 (98.5%) participated. Age- and sex-specific mean diastolic and systolic blood pressure readings are presented. The overall prevalence rate of hypertension was 13%; in 9.6% of those with hypertension the condition had previously been diagnosed. Blood pressure generally rose with increasing age, but diastolic pressure declined after age 50 in both sexes. The rate of obesity increased with increasing age; 70% of women aged 35 to 64 years and 50% of men aged 35 to 44 years were obese. Over half (56.4%) of the study population smoked, and most smokers were less than 35 years old.